Slope stability engineering developments and applications : proceedings of the international conference on slope stability organized by the Institution of Civil Engineers and held on the Isle of Wight on 15-18 April 1991 - Chandler, R. J. (Thomas Telford, 1991)
Brings together details on slope stability, causes of landslides, landslide prevention, several techniques for assessing and predicting stability, various methods for stabilising slopes, and the special considerations for coastal situations.